Public Service Innovation in the Era of Society 5.0: Data Protection, Governance, and Regulation in Indonesia - Diana, Diana; Salasaiah, Salasaiah; Boonsayan, Rungarun (Citra Media Publishing, 2025)
The rapid adoption of Society 5.0–oriented smart technologies in Indonesia’s public sector has generated both opportunities and controversies. While digital innovation promises efficiency and personalized services, it simultaneously raises pressing concerns about data protection, bureaucratic accountability, and regulatory adequacy. This study is based on the argument that innovation in public services cannot be separated from governance capacity and regulatory frameworks that safeguard inclusivity and ethical standards. Using a qualitative content analysis of online news coverage, the study identifies three major findings. First, controversies surrounding smart public services are primarily linked to weak mechanisms of data protection, transparency, and bureaucratic responsibility. Second, adaptive and collaborative governance emerges as a crucial prerequisite for managing the opportunities and risks of Society 5.0, highlighting both efficiency gains and persistent digital divides. Third, Indonesia’s regulatory framework remains reactive and fragmented compared to advanced countries, with significant gaps in institutional capacity, law enforcement, and ethical AI standards. The findings contribute to the growing body of literature on digital governance by emphasizing the interplay between innovation, regulation, and governance in emerging economies. The study underscores that the effectiveness of public service innovation in the digital era depends not only on technological readiness but also on political will, institutional resilience, and participatory governance. The need to integrate adaptive governance with proactive regulation; and practically, the urgency of strengthening data protection and fostering inclusive digital infrastructures. Without such efforts, the promise of Society 5.0 risks reinforcing inequalities rather than advancing social justice.